2021
DOI: 10.2478/psicolj-2021-0001
|View full text |Cite
|
Sign up to set email alerts
|

The ANTI-Vea task: analyzing the executive and arousal vigilance decrements while measuring the three attentional networks

Abstract: The vigilance decrement phenomenon has been traditionally studied by simple and monotonous behavioral tasks. Nowadays, however, there is considerable interest in measuring vigilance with more complex tasks, including independent measures of other attentional functions. In the present study, we provide evidence supporting the suitability of the Attentional Networks Test for Interactions and Vigilance – executive and arousal components (ANTI-Vea) as an appropriate method to simultaneously assess multiple attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 50 publications
(109 reference statements)
3
21
0
Order By: Relevance
“…Comparing Figures 7A,C , 9A,C , it is found that the decrease in concentration and arousal have the same phenomenon in the functional brain network of low-frequency EEG, indicating that there is a certain correlation between attention and arousal. This corroborates the theory that decreased attention is attributed to decreased physiological arousal ( Luna et al, 2021 ). However, the difference degree is much smaller than the difference degree between the fatigue and the resting state, which shows that there is also the difference between the decline of attention and the decline of arousal from another perspective.…”
Section: Resultssupporting
confidence: 90%
“…Comparing Figures 7A,C , 9A,C , it is found that the decrease in concentration and arousal have the same phenomenon in the functional brain network of low-frequency EEG, indicating that there is a certain correlation between attention and arousal. This corroborates the theory that decreased attention is attributed to decreased physiological arousal ( Luna et al, 2021 ). However, the difference degree is much smaller than the difference degree between the fatigue and the resting state, which shows that there is also the difference between the decline of attention and the decline of arousal from another perspective.…”
Section: Resultssupporting
confidence: 90%
“…Using G * Power 3.1.9.4 (Faul et al, 2007), power analysis showed that considering α = 0.05 and 1β = 0.90, the minimum sample size required to observe a decrease in hits across blocks considering an effect size of η 2 p = 0.05, two sessions, and seven blocks, was of 35 participants (i.e., as the final sample included in data analysis). Given that in the present study participants performed two experimental sessions of seven blocks, the statistical power of our study was much higher than in previous studies with a lower number of trials (i.e., one session of six blocks in Luna et al, 2018Luna et al, , 2021aBaker et al, 2021).…”
Section: Participantsmentioning
confidence: 70%
“…Sample size was a-priori estimated based on previous studies with 40 participants per group in which the decrement in hits across six blocks measured with the ANTI-Vea showed an effect size of η 2 p = 0.05 (Luna et al, 2018(Luna et al, , 2021a. Using G * Power 3.1.9.4 (Faul et al, 2007), power analysis showed that considering α = 0.05 and 1β = 0.90, the minimum sample size required to observe a decrease in hits across blocks considering an effect size of η 2 p = 0.05, two sessions, and seven blocks, was of 35 participants (i.e., as the final sample included in data analysis).…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations